2018
DOI: 10.1080/07420528.2018.1505752
|View full text |Cite
|
Sign up to set email alerts
|

The association between circadian rest-activity patterns and the behavioral and psychological symptoms depending on the cognitive status in Japanese nursing-home residents

Abstract: Of these models, the multi-level model provided grounds for our proposal that the fragmentation or the amplitude of rest-activity parameters might be associated with the outcome of BPSD, considering the cognitive status of older individuals in different facilities. The findings offer practical insight into the prevention of BPSD and the improvement of rest-activity rhythms in rehabilitative care in nursing homes.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 26 publications
0
12
1
Order By: Relevance
“…Cross-sectional studies( Table 1 ): Consistent evidence demonstrated that people with dementia had less stable rhythms (5/6 studies 38). For example, the recent work by Saito et al (5) demonstrated that, among nursing home residents, those with dementia had lower IS values (reflecting less stability across days). The one study (8) that failed to detect an overall statistically significant overall association between dementia and RAR stability did find stability was lower among people with dementia who were living in institutional settings (compared with community dwelling people with dementia and healthy controls); the sample of people with Alzheimer’s disease living independently in this study was small (n = 8).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cross-sectional studies( Table 1 ): Consistent evidence demonstrated that people with dementia had less stable rhythms (5/6 studies 38). For example, the recent work by Saito et al (5) demonstrated that, among nursing home residents, those with dementia had lower IS values (reflecting less stability across days). The one study (8) that failed to detect an overall statistically significant overall association between dementia and RAR stability did find stability was lower among people with dementia who were living in institutional settings (compared with community dwelling people with dementia and healthy controls); the sample of people with Alzheimer’s disease living independently in this study was small (n = 8).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, 4/6 studies (positive studies (3, 4, 7, 9 and nonsignificant studies 5, 8) found that cognitive impairment was related to higher RAR fragmentation. For example, the early work by Wittin et al (3) demonstrated that Alzheimer disease patients had higher intra-daily variability, reflecting more fragmented (less consistent) rhythms.…”
Section: Resultsmentioning
confidence: 99%
“…These disruptions predominantly include fragmentation and a reduced amplitude of the 24-h activity rhythm, and behaviors such as "sun-downing" [27] and frequent daytime napping [28]. Recent cross-sectional studies report a lower amplitude [28][29][30], a lower stability [29,31], and more fragmentation [29] in patients with dementia. More fragmented 24-h activity rhythms were also found in persons with earlyonset dementia [32].…”
Section: -H Activity Rhythms and Neurodegenerative Diseasementioning
confidence: 99%
“…[24][25][26] Sleep problems are common among nursing home residents 27 and people suffering from dementia, 28 and have been linked to increased morbidity and mortality, cognitive decline 29 and additional symptoms such as agitation, hallucinations, depressed mood and disturbed appetite. 30,31 Studies have found that exposure to bright light can improve sleep and entrainment of circadian rhythms, 32 as well as ameliorate aggressive behavior and depression [33][34][35] in people with dementia, suggesting that dementia patients are exposed to inadequate levels of illuminance.…”
Section: Introductionmentioning
confidence: 99%